Implementation of Islamic Education Management to Realize a Superior Education Institution - Murdianto Murdianto (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
The implementation of Islamic education management principles is a key aspect of building excellent educational institutions. This study aims to analyze the impact of the integration of Islamic values in education management on the quality and sustainability of educational institutions. This research method uses a qualitative approach. Data were collected through interviews with institutional leaders, lecturers, students, and alumni. In addition, participatory observation and secondary data supported the findings from primary data. Data analysis was conducted using an inductive approach. The results showed that principles such as fairness, transparency, participation, and accountability play an important role in improving the quality of learning, student character, and the efficiency of resource management. So, this research confirms that there is a need for the relevance of the Islamic education management approach. Integration of Islamic values not only improves the quality of learning and academic achievement of students, but also strengthens the character, participation, and accountability of educational institutions. Thus, the Islamic education management approach has a significant contribution to the development of sustainable and meaningful education